Price Squeeze in Practice: Is it a Profitable Strategy? - Demetrius Yannelis (International Telecommunications Society (ITS), 2010)
Price squeeze has been an important issue in the telecommunications market as many incumbent operators have exercised this strategy in order to foreclose competitive entrants (see Polo (2008), Bravo and Siciliani (2007), Geradin and O'Donoghue (2005) and Crocioni and Veljanovski (2003). The experience in all European cases considered in these studies shows the difficulty and complexity faced by regulators in implementing the imputation analysis. In the US some Courts have followed a different approach and some authors do not consider margin squeeze as an abuse by a dominant operator (see also Crandall and Singer (2007), Carlton (2008) and Sidak (2008)). The role of the present paper is to examine critically the decision of the Greek regulator on a price squeeze allegedly applied by the Greek incumbent OTE through its subsidiary OTEnet on the market for broadband services. In doing so, a number of important questions arise: Why the regulator used the REO test instead of the EEO test that has been applied in almost all antitrust cases? What is a legitimate or sufficient margin under which a margin squeeze occurs? Can a price squeeze lead to falling market shares for the incumbent and rising market shares for the entrants? Should the NCA intervene just after one year from the opening of the market? In this paper we attempt to answer the above questions and relate our results to the existing literature.
Keywords: 330